Vulnerabilidade ambiental em estuários tropicais: ferramentas e modelo conceitual para gestão - Nascimento, Regina Célia Macêdo do (2024)
Estuaries are complex environments of extreme importance from both ecological and socio-economic perspectives. However, they face threats from unplanned occupations and ecosystem and social fragilities. Therefore, the objective of this research was to identify and analyze the components and existing tools related to environmental vulnerabilities for possible application in tropical estuarine regions, aiming to propose a conceptual model for managing these regions, using the Capibaribe River estuary, located in Recife (state of Pernambuco, Brazil), as a case study. To achieve this objective, a Systematic Literature Review was conducted to identify the main environmental vulnerabilities in tropical estuaries and the applicable tools for managing these environments. From the review, vulnerabilities related to climate change and anthropogenic actions were identified, such as: sea-level rise; flooding; coastal erosion; discharge of urban pollutants; excess nutrients in the water; and oil spills. Additionally, when considering the adaptive capacity of estuaries, three fundamental aspects stand out: the participation of social actors; the protection of the estuarine ecosystem; and integrated management. The review also identified and analyzed 14 tools that can support the management and analysis of vulnerability related to climate change. These tools include, among other functionalities, the use of satellite images, georeferencing systems, and numerical modeling. Using the Pugh Matrix, the main potentialities and weaknesses of each tool were evaluated in relation to their use in estuaries, and possibilities for integrating them into a conceptual model for the Capibaribe River estuary were explored. The conceptual model was structured into four integrating units (exposure components and affected environmental processes; tools for vulnerability analysis; integrated management; and improvements for the estuary). Its structure provided a comprehensive view of vulnerability in estuaries, favoring guidelines and possibilities for tools to be used for integrated environmental management of the Capibaribe River estuary and the consequent preservation of this important estuarine ecosystem. The conceptual model developed becomes an ally in understanding environmental vulnerability in these regions and can be adapted to other estuarine locations.